2011
DOI: 10.1111/j.1464-410x.2011.10761.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based study of erectile dysfunction and polypharmacy

Abstract: What ' s known on the subject? and What does the study add?It is known that medical conditions such as diabetes, high blood pressure, high cholesterol, smoking and prescribed medications cause erectile dysfunction (ED). This has been studied at the molecular level and reported in population studies. The present study shows that, after accounting for known medical problems, there is a doseresponse relationship, in which worsening degrees of ED are seen when a greater number of medications are taken, regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Moreover, we lacked data about the potential impact that drugs, either taken individually or together for various comorbid conditions, may eventually have on erectile functioning. Indeed, there are data suggesting that the number of medications a man takes is associated with worse ED even after comorbidities have been taken into account [6,38,39,52]. Similarly, our analyses did not take into consideration cigarette smoking and other recreational habits that had been already clearly associated with ED of various degrees of severity, with data also suggesting a potential interaction with the patient's medical history [46,48,53,54].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, we lacked data about the potential impact that drugs, either taken individually or together for various comorbid conditions, may eventually have on erectile functioning. Indeed, there are data suggesting that the number of medications a man takes is associated with worse ED even after comorbidities have been taken into account [6,38,39,52]. Similarly, our analyses did not take into consideration cigarette smoking and other recreational habits that had been already clearly associated with ED of various degrees of severity, with data also suggesting a potential interaction with the patient's medical history [46,48,53,54].…”
Section: Discussionmentioning
confidence: 92%
“…The global prevalence of ED as assessed by the MMASderived self-assessment was 15.5-69.2% (Table 2 [12,[28][29][30][31][32][33][34][35][36]). The prevalence of ED by continent was: 22.0-57.8% [12,32,36], 15.5-55.2% [29][30][31]34,35], 17.2% [30], 60.69 [28], 22.4-69.2% [30,33], for North America, South America, Europe, Oceania and Asia, respectively. The prevalence of ED increased with increasing age where the study population was aged >40 years [29,[31][32][33][34].…”
Section: Ed Prevalencementioning
confidence: 99%
“…Martins et al [29] studied a young (aged 18-40 years) population of men in Brazil and found a higher prevalence of ED amongst those aged 18-25 years (35.6%) compared to those aged 26-40 years (30.7%). The prevalence of ED was inversely associated with ED severity, 25.1-36.7%, 8.5-25.0%, 1.3-16.77% had mild, moderate, and severe ED, respectively [12,28,31,[33][34][35][36]. Derby et al [12] measured ED prevalence using both the IIEF and MMAS self-assessment methods.…”
Section: Ed Prevalencementioning
confidence: 99%
“…Whether prescription medication use contributes to ED in addition to the effect of the illness itself remains controversial. Overall, an increase in the number of prescription medications has been associated with increased odds of ED . Results from the National Health and Nutrition Examination Survey (NHANES) and the Health Professionals Follow‐up Study (HPFS) suggest that AHT and antidepressant use may increase the risk of ED .…”
Section: Introductionmentioning
confidence: 99%